A new model to guide identity-focused multidisciplinary rehabilitation for children and young people following acquired brain injury: I-FoRM. Issue 8 (14th September 2022) - Perkins, Alison; Gracey, Fergus; Kelly, Gemma; Jim, Jenny
ABSTRACT: A complexity of biological, psychological, environmental and systemic factors influences a child's adaption after acquired brain injury (ABI), all of which transform as the child matures. Multidisciplinary rehabilitation teams are challenged by balancing family system needs and the child's needs, whilst promoting the child's functional skills in difficult or unappealing tasks. This paper presents the conceptual basis for a model for use in childhood ABI neurorehabilitation to address these challenges. A non-systematic narrative review of literature pertinent to integrated neurorehabilitation of pediatric ABI was conducted. Contemporary models of adult and pediatric psychosocial adaptation involving identity following ABI were reviewed. Key findings were then synthesized with models of pediatric resilience and self-concept development. The resulting model describes a cyclical adaptation process whereby the child learns experientially about their self and their world after ABI. Processes of identity development play a central role – particularly emotive processes of self-evaluation – by influencing the child's motivation for participation, tolerance for challenge, self-regulation and emerging self-awareness. The model directs clinicians to use the psychosocial processes of identity development to enhance the child's willingness and capacity to engage in the daily challenges of rehabilitation. Further systematic development and evaluation of the model is needed.